Rapid Adaptation Effect of N170 for Printed Words. Issue 1 (August 2014) - Cao, Xiao-Hua; Jiang, Bei; Li, Chao; He, Zi-Qiao
Faces and written words are two of the most familiar types of visual patterns with the brain's selective response of N170 component in early perception. Using ERP adaptation paradigms, studies have found the N170 response is reduced when there is repeated presentation of upright faces relative to a control condition. In contrast to these well-established features of the face-related N170 adaptation effect, the characteristics of the N170 adaptation effect for printed words are less clear. The goal was to investigate the ERP adaptation effects of printed language (English words and Chinese characters) in a short ISI (200msec.) adaptation paradigm. The present study showed that both alphabetic words and non-alphabetic words could produce a rapid N170 adaptation effect. Objects of expertise (e.g. words and faces) can produce a rapid N170 adaptation effect but other objects (e.g., houses) cannot, indicating that the specific stimuli have some specific mechanisms for the rapid N170 adaptation.